(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2017)
Introduction: Many molecular methods of identification of mycobacteria are now available. With many molecular consumables now being available at low prices, routine identification in clinical laboratories is now possible, even in low/ middle income settings that have basic molecular facilities. This study was conducted to optimize a low cost PCR-RFLP based identification that can be used in such a laboratory. Methodology: DNA was extracted from mycobacterial cultures using five methods. Three were heat extraction and two were kit extraction methods. Yield and purity of extracted DNA was evaluated and PCR-RFLP was done on extracts to ensure that the DNA could be used for molecular assays. The method giving the highest yield at low cost was selected and DNA was extracted from 105 mycobacterial cultures from patients diagnosed with pulmonary tuberculosis. hsp65 PCR and restriction digestion with BstEII and HaeIII enzymes was done to identify mycobacteria, differentiate MTB complex from NTM and identify NTM species. gyrBPCR and restriction digestion with RsaI was done to identify MTB complex species. hsp65partial sequencing was done to confirm NTM species. Costs for molecular identification were calculated based on consumable cost. Results: Heat extraction in water (80 0C for 1 hour) provided a mean DNA yield of 30.07ng/μland mean A260/280 ratio of 1.45. Heat extraction methods gave significantly higher DNA yield compared to the kit extraction methods (ANOVA, p<0.05). hsp65 PCR-RFLP identified 102 isolates as MTB complex and 3 isolates as NTM. gyrBPCR-RFLP confirmed the 102 isolates as MTBC and showed that all isolates belonged to the MTB/ M africanum/ M canettiigroup. Hsp65 partial sequencing identified the NTM as 2 isolates of M aviumand 1 isolate that could not be identified. An algorithm for PCR-RFLP based identification was developed that allows identification of mycobacterial isolates at low cost (approximately USD 6.00 per sample). The NTM rate in this study population was 2.6%. Conclusions: Using heat extraction in water, PCR-RFLP based identification of clinical mycobacterial isolates can be established at low cost in a laboratory that has basic molecular facilities. SAARC J TUBER LUNG DIS HIV/AIDS, 2016; XIII(1), page: 23-31